1993
DOI: 10.1254/jjp.62.257
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profiles of Muscarinic Receptors in the Longitudinal Smooth Muscle of Guinea Pig Ileum

Abstract: ABSTRACT-We characterized the pharmacological nature of the tachykinin receptor subtype mediating the contractile response to electrical transmural stimulation (ETS) in the isolated rabbit iris sphincter muscle preparation by using selective NK,-receptor antagonists, spantide and L-668,169, and a selective NK2-recep tor antagonist, L-659,877. ETS caused a biphasic contraction in this preparation: a rapidly developing cholinergic component followed by a slowly decaying tachykininergic component. The tachykinine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
3
0
3
Order By: Relevance
“…These results suggest that NKA acts on NK1 rather than NK2 receptors in the neonatal rat spinal cord. The possibility that NKA acts on NK1 receptors has also been suggested in other preparations (Kunitomo et al, 1993;Zhao et al, 1993).…”
Section: Discussionmentioning
confidence: 91%
“…These results suggest that NKA acts on NK1 rather than NK2 receptors in the neonatal rat spinal cord. The possibility that NKA acts on NK1 receptors has also been suggested in other preparations (Kunitomo et al, 1993;Zhao et al, 1993).…”
Section: Discussionmentioning
confidence: 91%
“…The prominent innervation of the iris sphincter muscle is of relevance, as NKA has been shown to contract this muscle in the rat, 35 rabbit, 36 -41 and pig 42 via activation of NK-1 receptors, at least in the rabbit. 41 Miosis induced by peptides deriving from the TG is well known to occur in response to topical noxious stimulation in lower mammals and has been shown to be mainly mediated by SP (see review, see Ref. 43).…”
Section: Discussionmentioning
confidence: 99%
“…To address the role of the muscarinic and nicotinic ACh receptors on the responses triggered by ACh, the ileum sections were incubated for 15 min with 0.2 µM AF-DX 116, a selective muscarinic acetylcholine receptor (mAChR) M2 antagonist; 0.1 µM 4-DAMP, a specific mAChR M3 antagonist; 10 µM mecamylamine, non-selective nicotinic acetylcholine receptors (nAChR) α3 and β4 antagonists; or 2 nM α-bungarotoxin, a specific α7 nicotinic acetylcholine receptor (nAChR) antagonist, prior to the performance of the 0.1–10 µM ACh concentration–response curves. Previous studies have reported that similar concentration ranges of these antagonists induce effects in the neurotransmission of the intestinal smooth muscle [ 24 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%